Cover Feature: Dipyrrolyldiketone PtII Complexes: Ion‐Pairing π‐Electronic Systems with Various Anion‐Binding Modes (Chem. Eur. J. 39/2021). Issue 39 (14th June 2021) - Kuno, Atsuko; Hirata, Goki; Tanaka, Hiroki; Kobayashi, Yoichi; Yasuda, Nobuhiro; Maeda, Hiromitsu
Abstract : Synthesis of dipyrrolyldiketone Pt II complexes, as phosphorescence anion‐responsive π‐electronic molecules, was motivated by the chemistry of previously investigated boron complexes. The Pt II complexes displayed solid‐state ion‐pairing assemblies, exhibiting various anion‐binding modes, derived from pyrrole‐inverted and pyrrole‐non‐inverted conformations, and packing structures, with the contribution of charge‐by‐charge assemblies. More information can be found in the Full Paper by H. Maeda et al. (DOI: 10.1002/chem.202100855 ).